Níveis de atividade física e fatores associados em adultos moradores de zona rural. - Martins, Rafaela Costa (2017)
Background: The purpose of this study was to test reliability of the Global Physical Activity Questionnaire (GPAQ) in a Brazilian rural population, and to evaluate its concurrent validity using accelerometers. Methods: Fifty-five adults (18+ years) living in a rural Brazilian city were selected to wear an accelerometer for one week and to answer the GPAQ twice in a week period interval. Reliability was verified according to results from questionnaire using Intraclass Correlation Coefficients (ICC). The concurrent validity was analyzed based on Pearson’s correlation and Bland and Altman’s diagrams between accelerometer- based physical activity and GPAQ. Results: We found relatively high reliability parameters for the total physical activity (ICC=0.78; 95%CI 0.63 – 0.87). The average difference between both GPAQ measures was 192 minutes (95%CI -69.6 – 453.7) and wider differences were found when participants reported more than 400 minutes of physical activity per week, approximately. There was a moderate correlation between accelerometer and GPAQ (r=0.5). However, among those reporting high physical activity there was limited agreement between these measures (total average difference=-1043 minutes (95%CI - 1452.2 – -634.1). Conclusion: GPAQ presented acceptable reliability and validity parameters to differentiate those who achieve from those who does not achieve the recommendations, and can be used in rural populations. However, there is still a need for new instruments for this population group.